2009
DOI: 10.2337/db09-0755
|View full text |Cite
|
Sign up to set email alerts
|

Grp78 Heterozygosity Promotes Adaptive Unfolded Protein Response and Attenuates Diet-Induced Obesity and Insulin Resistance

Abstract: OBJECTIVETo investigate the role of the endoplasmic reticulum (ER) chaperone glucose-regulated protein (GRP) 78/BiP in the pathogenesis of obesity, insulin resistance, and type 2 diabetes.RESEARCH DESIGN AND METHODSMale Grp78+/− mice and their wild-type littermates were subjected to a high-fat diet (HFD) regimen. Pathogenesis of obesity and type 2 diabetes was examined by multiple approaches of metabolic phenotyping. Tissue-specific insulin sensitivity was analyzed by hyperinsulinemic-euglycemic clamps. Molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
131
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(140 citation statements)
references
References 41 publications
8
131
1
Order By: Relevance
“…1A-C). Thus, partial silencing of BiP is sufficient to cause UPR, as also noted by others (Ye et al, 2010). A more complete ablation of BiP is provided by using subtilase AB (subAB), a bacterial endopeptidase which cleaves BiP specifically at a dileucine motif (L416-L417), rendering it nonfunctional (Paton et al, 2006).…”
Section: Resultsmentioning
confidence: 78%
“…1A-C). Thus, partial silencing of BiP is sufficient to cause UPR, as also noted by others (Ye et al, 2010). A more complete ablation of BiP is provided by using subtilase AB (subAB), a bacterial endopeptidase which cleaves BiP specifically at a dileucine motif (L416-L417), rendering it nonfunctional (Paton et al, 2006).…”
Section: Resultsmentioning
confidence: 78%
“…S2A). In contrast to other tissues where GRP94 was up-regulated to compensate for GRP78 haploinsufficiency (29), the level of GRP94 in the ductal structures was similar in the PKC and PKC78 f/+ mice (Fig. S2A).…”
Section: Resultsmentioning
confidence: 82%
“…A recent study showed that arctigenin served as an anti-tumour agent by blocking the expression of unfolded protein response (UPR) target genes [25]. Although UPR has been reported to be involved in the pathophysiology of insulin resistance and diabetes [26][27][28], our preliminary work showed that arctigenin had no effects on UPR or the Jun N-terminal kinase (JNK) pathway in liver of ob/ob mice (ESM Fig. 2).…”
Section: Discussionmentioning
confidence: 77%